A Brickworker Becomes Transformative STEAM Educator: Journey of Resistance, Advocacy, and Envisioning - Manandhar, Netra Kumar (Journal of Transformative Praxis, 2022)
My journey from brick worker to STEAM education was/is characterized by resistance, advocacy, and envisioning. Surrounded by pains, sufferings, hurdles, and economic adversities, I spent more than 18 years in several brick factories resisting the economic vulnerabilities. At the same time, I faced tremendous difficulties in educating myself in the formal and conventional/traditional nature of educational models. The similar contexts led my upper higher education till B.Ed. in mathematics education. The duration of more than three years in my master’s in mathematics education, and MPhil in STEAM education was a precious moment for me to start my journey of resisting, advocating, and envisioning life and educational practices. The journey from a brick worker to STEAM educator was the biggest challenge for me. I accepted the challenges put by my life and education system and tackled them to become more skillful, knowledgeable, and aware to solve them and develop alternative practices which are more authentic, open, critical, empowering, and inclusive for myself and others. Thus, this research portrays my journey of resisting disempowering educational practices, advocating progressive and empowering practices, and envisioning a transformative educational perspective via autoethnography as a methodology and transformative learning theory as a theoretical referent. The research is useful for educators and others to bring quality and meaningful changes in educational practices for sustainable development in education and life.